Impaired Anorectal Afferents Is a Potential Pathophysiological Factor Associated to Functional Anorectal Pain - Zhang, Qi; Liu, Yanni; Zhang, Qiong; Zhang, Yuqing; Wu, Sangsang; Jiang, Bin; Ni, Min (Frontiers in Neurology, 2020)
Background / aims: Functional anorectal pain (FARP) is a common disease in anorectal region, which belongs to chronic pelvic floor pain. The mechanisms of its development are not fully understood. We designed this experiment to evaluate the characteristics of rectal sensory evoked potential (RSEP) and anorectal manometry (ARM) in this population, so as to explore the pathophysiology of FARP. Methods: The rectal sensory evoked potentials (RSEP) and anorectal manometry (ARM) were performed in 23 patients with FARP and 23 healthy controls. The correlation between the two measurements was investigated. Results: The results of RSEP showed that 1) the median latency to the first positive peak was 69.2±15.9 ms in patients, compared with 46.5±5.8 ms in controls (P = 0.000). 2) The amplitude of evoked potential peaks in the FARP patients was significantly lower than the healthy controls (P1/N1: P=0.049; N1/P2: P=0.010). 3) Compared with the controls, the patients showed a lower maximum voluntary squeeze pressure (P = 0.009), lower rectum (P = 0.007) and anal sphincter pressures (P = 0.000) during strain; and increased maximum tolerance threshold to rectal distention (P = 0.000). 4) The resting pressure of the anal sphincter was correlated with the peak amplitude of the RSEP (P1/N1: r=0.537, P=0.039; N1/P2: r=0.520, P=0.047). Conclusions: The RSEP can be used to evaluate the ascending sensory pathway of the brain-gut axis; it can provide an objective evidence for the neuropathy of FARP. The longer latency and lower peak amplitude of RSEP indicate the functional defects of the anorectal afferent pathway. The correlation between the peal amplitude of the RSEP and the resting pressure of the anal sphincter suggests that the reduced anal pressure in patients may be related to the impairment in the afferent signaling pathway.